ANALISIS MANAJEMEN LOGISTIK OBAT DI GUDANG FARMASI PUSKESMAS KARANGMALANG KOTA SEMARANG - Novisa Hamdani; Fitri Indrawati (Jurnal Kesehatan Masyarakat (Undip), 2022)
The highest increase of damaged or expired drugs at Karangmalang Healthcare Center in 2020 was 48,060 drugs, caused a stock accumulation. As of January to March 2021, it was reported that 2,739 drugs were damaged or expired and out of stock during the pandemic. Stock outs and stagnant drug could result in drug logistics management not going well. The purpose of this study was to determine the logistics management of drugs in the pharmacy warehouse of Karangmalang Pimary Healthcare Center Semarang City. Qualitative study was applied in this research. The informant is an employee of the Karangmalang Primary Healthcare Center Semarang City, with purposive sampling. Data is processed and presented in narrartive form. From the input aspect, it was found that in terms of funds, it was quite good, but for drug management staff there had never been any training, inadequate facilities and infrastructure and incomplete prosecures. Aspects of the  process for planning and procurement often occur vacancies, inadequate drug storage because it had a small building size, as well as recording and report in there were still missed drugs or even excess stock which result in a lot of damaged/expired drugs. The output aspect of drug availability is currently in accordance with the needs, but its implementation had not been effective and efficient because there were still vacancies, expired/damaged, and missed drugs.Suggenstions for the Karangmalang Primary Healthcare is to carry out routine evaluations of drug management and renovate inadequate drug storage warehouse.